2017
DOI: 10.3201/eid2302.161095
|View full text |Cite
|
Sign up to set email alerts
|

Changing Epidemiology of Hepatitis A and Hepatitis E Viruses in China, 1990–2014

Abstract: We compared the epidemiology of hepatitis A and hepatitis E cases in China from 1990–2014 to better inform policy and prevention efforts. The incidence of hepatitis A cases declined dramatically, while hepatitis E incidence increased. During 2004–2014, hepatitis E mortality rates surpassed those of hepatitis A.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
24
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 14 publications
5
24
0
3
Order By: Relevance
“…A comparatively lower HAV prevalence may be due to improved living standards environmental hygiene and increasing Hepatitis A immunization. Other Indian authors also observed the similar finding (Chandra et al, 2012;Ren et al, 2017).…”
Section: Resultssupporting
confidence: 71%
“…A comparatively lower HAV prevalence may be due to improved living standards environmental hygiene and increasing Hepatitis A immunization. Other Indian authors also observed the similar finding (Chandra et al, 2012;Ren et al, 2017).…”
Section: Resultssupporting
confidence: 71%
“…It is plausible that this might be accounted for by the improved sanitary infrastructure, which has asserted a negative ecological pressure on HEV gt1. In China, acute HEV infection is more common than HAV infection (Ren et al 2017).…”
Section: Asiamentioning
confidence: 99%
“…China licensed the world’s first live attenuated liquid hepatitis A virus (HAV) vaccine in 1992. Since the same year, the HAV vaccine has been offered in schools and universities, as well as to those who were vulnerable and had close contact with those infected with HAV 8 25 26. This coincides with the dramatic drop in VH mortality for those born between 1970 and 1974 as this group was the cohort who received the vaccination either at school or university.…”
Section: Discussionmentioning
confidence: 99%
“…The emerging challenges in VH prevention and control, which have already caused a resurgence in VH mortality, are mainly due to the increasing epidemic of hepatitis E virus (HEV) and hepatitis C virus (HCV) in more recent years. Regarding HEV, although the number of reported deaths resulting from HBV remained largely unchanged since 2007, accounting for nearly 80% of all VH deaths in China,1 4 27 29 the incidence and mortality rate of HEV rose, overtaking those of HAV in 2011 and 2004, respectively 26 27 30. It is anticipated that the availability of the HEV vaccine may eventually curb the rising epidemic of HEV 10.…”
Section: Discussionmentioning
confidence: 99%